Distribution of mosquito larvae in various breeding sites in National Zoo Malaysia - Muhammad Aidil, Roslan; Imelda, A.; Jeffery, J.; Romano, Ngui; Wan Yusoff, Wan Sulaiman; Yvonne Ai Lian, Lim; Rohela, Mahmud (Malaysian Society of Parasitology and Tropical Medicine, 2015)
Mosquitoes are principal vectors of major vector-borne diseases. They are widely found throughout urban and rural areas in Malaysia. They are responsible for various vectorborne diseases such as dengue, malaria, filariasis and encephalitis. A total of 158 mosquito larvae specimens were collected from the National Zoo, Malaysia, from 11 types of breeding habitats during the study period from end of May 2007 to July 2007. Aedes albopictus was the predominant species (35.4%), followed by Tripteroides aranoides (26.6%), Lutzia halifaxii (11.4%), Aedes alboscutellatus (10.1%), Aedes caecus (8.9%), Armigeres spp. (4.4%), Malaya genurostris (2.5%) and Culex vishnui (0.6%). It is important to have a mosquito free environment in a public place like the zoo. Routine larval surveillance should be implemented for an effective mosquito control program in order to reduce mosquito population.